Analysis of Critical Thinking Skills Among Elementary School Students in Boyolali Regency - Fytra, Fytra; Rintayati, Peduk; Santosa, Eka Budhi (Universitas Sebelas Maret, 2026)
This study aims to analyze the critical thinking skills of elementary school students in Boyolali Regency through a systematic review of reputable articles. The method used was a Systematic Literature Review (SLR) with the PRISMA model, which involved four stages: identification, selection, eligibility, and inclusion. From an initial search on Google Scholar, which yielded 2,420 articles (2020-2026), 7 articles were found to meet the research criteria. The results of the analysis show that the critical thinking skills of elementary school students in Boyolali Regency can be improved through various approaches, including the application of innovative learning models such as Problem-Based Learning (PBL) and Discovery Learning, the development of technology-based learning media such as Potaki media, and the influence of external factors such as parenting styles. The studies reviewed showed a significant increase in students' critical thinking skills, with a completion rate of 91.7% to 95% after the implementation of learning interventions. These findings indicate that a combination of contextual learning strategies and family environmental support plays an important role in developing the critical thinking skills of elementary school students. This study concludes that evidence-based interventions integrating innovative pedagogy with supportive family environments are essential to fostering 21st-century critical thinking competencies among primary school students in Boyolali Regency.